MODELLING AND ANALYSIS OF SINGLE POINT CUTTING TOOL USING FEM METHOD - Batte Neela Krishna , N Nagesh M.Tech., Ph.D, K Ganesh M.Tech., Ph.D, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The finite element method is used to study the effect of different rake angles on the force exerted on the tool during cutting. Researchers use this method to better understand the mechanisms of chip formation, the generation of heat in cutting zones, as well as the characteristics of tool-chip interfacial friction on machined surfaces. This study investigates the variation in values of Vonmisses stress for three different rake angles for specified applied forces. The value of Vonmisses stress decreases as rake angle is increased. In present study, mesh is created in ANSYS and the boundary conditions are applied and the analysis is carried out for the applied constraints. The results calculated on software can be verified